2017
DOI: 10.4081/ejh.2017.2762
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-like, oxidized low-density lipoprotein receptor-1-deficient mice show resistance to age-related knee osteoarthritis

Abstract: The lectin-like, oxidized low-density lipoprotein (ox-LDL) receptor-1 (LOX-1)/ox-LDL system contributes to atherosclerosis and may be involved in cartilage degeneration. The purpose of this study was to determine whether the LOX-1/ox-LDL system contributes to age-related osteoarthritis (OA) in vivo, using LOX-1 knockout (LOX-1 KO) mice. Knee cartilage from 6, 12, and 18-month old (n = 10/group) C57Bl/6 wild-type (WT) and LOX-1 KO mice was evaluated by determining the Osteoarthritis Research Society Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…In addition, it was also identified that the production of Runx2 was gradually increased as the rats aged. Therefore, we hypothesized that Runx2 may also be involved in age-associated OA ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also identified that the production of Runx2 was gradually increased as the rats aged. Therefore, we hypothesized that Runx2 may also be involved in age-associated OA ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“… 26 The positive cell rate of LOX-1, ox-LDL, and MMP-3 in chondrocytes was also measured as previously described. 15 , 16 The percentage of positive cells was measured as the number of stained cells relative to the number of total chondrocytes (mean [range]; 88.5 [78-102]) in the medial tibial plateau. The correlation between the cartilage degeneration score and the positive LOX-1 or ox-LDL cell rate in chondrocytes was also examined.…”
Section: Methodsmentioning
confidence: 99%
“… 14 We also demonstrated previously that the LOX- 1/ox-LDL system contributed to the pathogenesis of instability-induced and age-related knee osteoarthritis using LOX-1 KO mice. 15 , 16 A recent report showed that LOX-1 expression was detected in the chondrocytes of patients with rheumatoid arthritis (RA) and that matrix metalloproteinase-3 (MMP-3) expression was increased by stimulation of ox-LDL. 10 Ishikawa et al also reported that the LOX-1 signal has a possibility as a biomarker and therapeutic target in human RA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, LOX-1 plays a pivotal role in the development of atherosclerosis, by inducing oxLDL uptake, lipidosis, foam cell generation and ultimately atheroma plaque formation (62,63). This OxLDL/LOX-1 axis was also shown to play a role in cartilage degeneration during age-related osteoarthritis progression in the murine knee (64). Similarly, the triggering of LOX-1 by AGEs, contributes to diabetic complications such as atherosclerosis (65,66).…”
Section: Clec8a (Lox-1 Olr-1)mentioning
confidence: 99%